PENERAPAN MODEL PEMBELAJARAN KOOPERATIF PENDEKATAN STRUKTURAL NUMBERED HEADS TOGETHER (NHT) UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA PESERTA DIDIK KELAS VIII5 SMP NEGERI 17 PEKANBARU - Febi Sartika; Sakur Sakur; Suhermi Suhermi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This research is a classroom action research that aims to improve the learning process and improve student’s mathematic learning achievements. The researcher applied cooperative learning model structural approach of Numbered Heads Together at class VIII5 of SMP Negeri 17 Pekanbaru, academic year 2018/2019. The cooperative learning model structural approach of Numbered Heads Together employs students identification numbers to increase student’s sense of responsibility during the learning process. Data collection instrument in this study is observational activity sheets teachers and students, as well as math achievement tests. Sheet observations were analyzed using descriptive narrative, while math achievement tests will be analyzed using descriptive statistics. The descriptive analysis of the narrative is shown that the learning process of refinement occurs before action cycle I and cycle II. The results of this research showed an increasing number of students learning mathematics about knowledge of the basic score (34,2 %) to the first test (57,9 %) to the second test II (78,9 %). For the skills of basic score (13,2 %) to the first test (21,1 %) to the second test (31,6 %). Based on these findings it can be concluded that the application of the cooperative learning model structural approach Numbered Heads Together at class VIII5 SMP Negeri 17 Pekanbaru can improve the learning process and improve mathematic learning achievements of students in the subject matter of circle academic year 2018/2019.Key Words : Mathematic Learning Achievements, Cooperative Learning Model Structural Approach of Numbered Heads Together, Class Action Research.